Spectrophotometric Determination of Monosaccharide Composition of Wood (Pinus brutia Ten.) Using Artificial Neural Network Modelling - Yasar, Samim (Asian Journal of Chemistry, 2014)
Spectrophotometric data were used to estimate monosaccharide content in Pinus brutia Ten. (brutian pine) wood using artificial neural network (ANN) modelling. The monosaccharide composition of P. brutia Ten. samples ranged for glucose from 42.33 to 54.67 %, for mannose from 8.55 to 11.95 %, for xylose from 7.15 to 9.83 %, for galactose from 1.72 to 2.49 % and for arabinose from 1.19 to 1.65 %, based on extractive free dry wood. Three layered artificial neural network model with six hidden neurons gave in general better results with correlation R2 values between 0.9987 and 0.9916 in training and between 0.9984 and 0.9902 in testing. In validation, this model was scored with a small average relative error (1.2 %) fairly good.